ANALISIS GULIRAN DANA SIMPAN PINJAM KHUSUS PEREMPUAN (SPP) PNPM MANDIRI PERDESAAN DI KECAMATAN SAMATIGA - Triyanto Triyanto; Devie Agustiar (Prodi Sosiologi FISIP Universitas Teuku Umar, 2017)
The country's economic growth depends not only on export and industrial output from factories scattered throughout Indonesia. Factories and other large-scale companies only provide macro economic growth, in fact people can not enjoy the growth of the economy directly. Therefore, in order for the people to be prosperous, the State must boost economic growth through micro enterprises run in real terms by the (small) people themselves. In fact, it is difficult for small people to gain access to formal financial institutions to stimulate the growth of micro-enterprises in the community. Finally, the State makes it easy for its people to develop micro businesses managed by the community itself through a program of women's special savings and loans (SPP) PNPM Mandiri Perdesaan. Based on the results of the research shows that this program succeeded in increasing the growth of Micro Enterprises and able to absorb the work force in Kecamatan Samatiga. The SPP-PNPM program is able to generate the creativity of the community in entrepreneurship among the housewives. The SPPPNPMfund roll is used to form the community-run business such as making food andbeverage, raising, producing salted fish, and other businesses. Meanwhile, to run the new business is always needed human resources as a manager. Thus, the amount of effort in the community is directly proportional to the needs of the workforce, the SPP PNPM fund spools greatly affect the development of SMEs and labor. Key words: SPP PNPM, Savings and Loans, Samatiga, Aceh Barat.